Association between IL1R1 rs2234650 Polymorphism in Patients with Acute Lymphoblastic Leukemia Infected with HHV-6A - Ibrahim, Maryam Sabri; Salman, Halah Dawood; Alheany, Aya Raed; Al-Alwany, Shakir Hammad (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2025)
Background: Everyone contracts the common infection known as human herpesvirus 6 (HHV-6). Particularly associated with encephalitis, human herpesvirus 6B (HHV-6B) poses a risk of morbidity and death to recipients of allogeneic hematopoietic stem cell transplants. IL-1β and interleukin-1α (IL-1α) are critical for enhancing infection resistance. Objective: To ascertain whether HHV-6A and the IL1R1 rs2234650 gene polymorphism are related and could be risk factors for Iraqi infants developing acute lymphoblastic leukemia (ALL). Methods: This case-control study included 150 blood samples from 100 patients diagnosed with ALL and 50 from healthy subjects. The IL1R1 rs2234650 gene polymorphism was identified using the Sanger sequencing method, and HHV-6A using PCR. Results: Age group and sex were found to differ significantly. Of 100 samples, 32 percent had HHV6A. The polymorphism of the IL-1R1 rs2234650 gene revealed that the distribution of DNA polymorphisms according to C, C, G, C, T, and Gwas 30%, 28%, 16%, 8%, 6%, and 12%, respectively, in patients with ALL and 33.33%, 26.67%, and 16.67%, respectively. 3.33%, 13.33%, and 6.67% in the group that was deemed to be in apparently healthy control (AHC). The frequency of the polymorphism's genotype distribution varied significantly between the patient and control groups. Conclusions: HHV6A and IL1R1 rs2234650 polymorphisms of ALL variations may be risk factors in the pathophysiology of ALL in Iraqi children.